Review of forestry practices in caribou habitat in southeastern British Columbia, Canada - Stevenson, Susan K. (Rangifer, 1986)
Woodland caribou (Rangifer tarandus caribou) in southeastern British Columbia feed mainly on arboreal lichens in winter. Some modified forestry practices that have been used or proposed for caribou ranges are reviewed. Partial cutting results in the retention of some forage lichens. Partial cutting and small patch harvesting may improve lichen growth on the remaining trees. Retention of advanced regeneration and some residual trees may improve lichen growth in the remaining stand. Extension of the rotation age increases the amount of harvestable forest useful to caribou at any one time. Progressive cutting minimizes road access to caribou ranges, and may be combined with partial cutting. Most forestry practices intended to maintain lichen production will result in increased human activity in caribou ranges, unless road access is controlled. The management strategy selected depends on site conditions and on the relative importance assigned to the impact of habitat alteration and human activity on caribou.